Innovation in clinical trial methodologies : lessons learned during the Corona pandemic - Schuler, Peter M.D (Elsevier/Academic Press, 2021)
"Innovation in Clinical Trial Methodologies: Lessons Learned during the Corona Pandemic presents a selection of updated chapters from Re-Engineering Clinical Trials that feature innovative options and methods in clinical trials. The Coronavirus pandemic is an accelerator for digitalization in many industries, including clinical trials. This book considers best practices, alternative study concepts requiring fewer patients, studies with less patient interaction, the design of "virtualized" protocols, and moving from data to decisions. This book will be helpful to pharmacologists, physicians and clinical researchers involved in the process of clinical development and clinical trial design. Considers multiple digital and virtual strategies Explores best practices, including the use of reduced patient involvement Brings together expert, trusted information to increase the efficiency and effectiveness of clinical trials"--Publisher's description